Molecular Cytogenetics in the Era of Chromosomics and Cytogenomic Approaches - Liehr, Thomas (Frontiers in Genetics, 2021)
Here the role of molecular cytogenetics in the context of yet available all other cytogenomic approaches is discussed. A short introduction how cytogenetics and molecular cytogenetics were established is followed by technical aspects of fluorescence in situ hybridization (FISH). The latter contains the methodology itself, the types of probe- and target-DNA, as well as probe sets. The main part deals with examples of modern FISH-applications, highlighting unique possibilities of the approach, like the possibility to study individual cells and even individual chromosomes. Different variants of FISH can be used to retrieve information on genomes from (almost) base pair to whole genomic level, as besides only second and third generation sequencing approaches can do. Here especially highlighted variations of FISH are molecular combing, chromosome orientation-FISH (CO-FISH), telomere-FISH, parental origin determination FISH (POD-FISH), FISH to resolve the nuclear architecture, multicolor-FISH (mFISH) approaches, among other applied in chromoanagenesis studies, Comet-FISH, and CRISPR-mediated FISH-applications. Overall, molecular cytogenetics is far from being outdated and actively involved in up-to-date diagnostics and research.